INFLUENCE OF THE INSTITUTIONAL FRAMEWORK ON THE OPPORTUNITIES FOR DEVELOPMENT OF THE RAILWAY TRANSPORT IN BULGARIA IN THE CONTEXT OF THE EUROPEAN RAILWAY SYSTEM - Ivanova, Lyubov; Parvanov, Petar (Revista Inclusiones, 2020)
The railway transport is of a great importance for the economic and social development of a country. The railway transport is extremely important for the economic and social development of a country. This fully applies to a country such as the Republic of Bulgaria, moreover, that it is a part of the European space and, depending on the policy pursued by the country and the sustainability of its institutions in this direction, it can benefit from the forthcoming liberalization of the railway transport in the European Union, as well as to lose from it. In order the development of the Bulgarian railway transport to have a sustainable growth and to be economically and socially efficient, the State should create sustainable institutions which to provide security and reduce the transaction costs for the railway carriers.